Comparative in vitro analysis of anti-diabetic activity of Indo-Pak black cardamom (Amomum subulatum Roxb.) and Chinese black cardamom (Amomum tsao-ko Crevost et Lemaire) - Hussain, Syed Ammar; Hameed, Ahsan; Fu, Jingjing; Xiao, Haifang; Liu, Qing; Song, Yuanda (Progress in Nutrition, 2018)
Diabetes mellitus is a metabolic disorder of glucose metabolism. An indispensable strategy for the control of diabetes mellitus, especially diabetes type 2 and its harmful effects, is the efficient management of postprandial hyperglycemia. Amomum subulatum Roxb. and Amomum tsao-ko Crevost et Lemaire are considered useful for the treatment of diabetes mellitus in Indo-Pak region and P.R China respectively. In this study, all tested concentrations of aqueous (v/v) extracts of the seeds and rind showed significant inhibitory activity against α-amylase and α-glucosidase. It can be concluded that aqueous extracts of Amomum subulatum Roxb and Amomum tsao-ko Crevost et Lemaire dry fruit constitutes (seeds and rind) have the significant inhibitory activity against the two carbohydrate hydrolyzing enzymes and the presence of phytochemicals like flavonoids, saponins, and tannins etc may have contributed significantly to the inhibitory potential of plant extracts